Pooled prevalence and associated factors of traditional uvulectom among children in Africa: A systematic review and meta-analysis - Solomon Demis Kebede; Kindu Agmas; Demewoz Kefale; Amare Kassaw; Tigabu Munye Aytenew (PLoS ONE, 2025)
Background Traditional childhood uvulectomy (TCU) is an unregulated cultural practice associated with significant health risks, including infections, anemia, aspiration, and oral or pharyngeal injuries. The reuse of unsafe tools such as blades, needles, or thread loops exacerbates the spread of infectious diseases like HIV and hepatitis B. Despite its clinical significance, the pooled prevalence and associated factors of TCU have not been adequately examined through systematic reviews or meta-analyses. Objective This review and meta-analysis aimed to estimate the pooled prevalence and associated factors of TCU in some African countries. Methods This systematic review and meta-analysis adhered to the PRISMA 2020 guidelines. A comprehensive search was performed across multiple databases, including MEDLINE, ScienceDirect, Google Scholar, and African Journals Online, to identify relevant studies. A weighted inverse-variance random-effects model was employed to estimate the pooled prevalence and associated predictors of TCU. Heterogeneity among the included studies was assessed using a forest plot, I2 statistics, and Egger’s test, ensuring the robustness and reliability of the findings. Missing data was handled by random effect model and sensitivity analysis. Data extraction was conducted fromNovember 6 to December 23, 2023. Eligibility criteria Included studies focused on children aged birth to under 15 years, examining TCU defined as the partial or complete removal of the uvula by traditional healers. Participants Eleven primary studies comprising 7,231 children from some countries in Africa were included. Results Pooled estimate of TCU in some African countries was 40.98% (95% CI: 25.04–56.92; I2 = 99.61, P = 0.001). Mothers residing in rural areas were 2.45 times more likely to have a child experienced TCU compared to those in urban areas (AOR = 2.45; 95% CI: 1.59–3.32). Similarly, Mothers with a history of having a previous child who undergo TCU were 8.44 times more likely to seek the procedure for their other children compared to mothers without such a history (AOR = 8.44; 95% CI: 6.27–10.61). However, caution is warranted when interpreting these findings due to the significant heterogeneity reported across the included studies, which may influence the generalizability of the results. Conclusions Nearly two-fifths of children in some African countries experienced TCU, which was influenced by maternal history and rural residency. While most procedures did not result in hospitalization, significant health risks remain. These findings underscore the urgent need for targeted interventions within maternal and child health programs to address TCU and mitigate its associated morbidity in the affected countries across Africa. Prospero I.D. CRD42024498699.